Original paperCholinesterase inhibitors in the “real world” setting: rivastigmine versus donepezil tolerability and effectiveness study - Sobow, Tomasz; Kloszewska, Iwona (Archives of Medical Science, 2006)
Introduction: Comparative tolerability and effectiveness of donepezil and rivastigmine in clinical practice using a “real life” sample of patients diagnosed as having mild to moderate Alzheimer’s disease and treated in the memory clinic setting have not been properly studied to date. Material and methods: A retrospective, case records analysis of all patients (N=183) who had been prescribed either drug over the period of 3 years (1998-2000) and were seen for at least 6 months afterwards. Main outcome estimates were: for tolerability the likelihood to achieve recommended doses for both drugs and side effects profiles, for effectiveness clinical global impression of change (CGI) rating at 6 months after dose titration finished. Results: Numerically, more subjects on rivastigmine than on donepezil dropped out early due to side effects (14.6% vs 11.9%). A maximum approved dose (10 mg for donepezil and 12 mg for rivastigmine) has been achieved by significantly more patients on donepezil than on rivastigmine (p<0.001). Side effects profiles of both drugs were similar and equally contributed to the drop-out rate. The response rate defined as at least no change on CGI did not differ between the groups. Conclusions: Donepezil and rivastigmine are comparably tolerated and of similar clinical benefits in the “real life” population of non-selected patients with mild to moderate AD. The differences in tolerability reported in the randomized controlled trials might be attributed to the fixed schedules of reaching the target dose of rivastigmine.